2006
DOI: 10.4049/jimmunol.177.1.479
|View full text |Cite
|
Sign up to set email alerts
|

Altered CD4+ T Cell Phenotype and Function Determine the Susceptibility to Mucosal Candidiasis in Transgenic Mice Expressing HIV-1

Abstract: The impairments of protective mucosal immunity which cause susceptibility to oropharyngeal candidiasis (OPC) in HIV infection remain undefined. This study used a model of OPC in CD4C/HIV MutA transgenic (Tg) mice expressing Rev, Env, and Nef of HIV-1 to investigate the role of transgene expressing dendritic cells (DCs) and CD4+ T cells in maintenance of chronic oral carriage of Candida albicans. DCs were depleted in the Tg mice and had an immature phenotype, with low expression of MHC class II and IL-12. CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 61 publications
3
20
0
Order By: Relevance
“…Dendritic cells in CD4C/HIV MutA Tg mice have an immature phenotype, with low expression of major histocompatibility complex (MHC) class II and costimulatory molecules and a decreased capacity to present antigen in vitro (20,27). In view of the defective production of MCP-1 in the Tg mice, dendritic cells could potentially have failed to accumulate in the lungs in response to C. neoformans infection because of defective CCR2-mediated recruitment and differentiation of monocytes (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendritic cells in CD4C/HIV MutA Tg mice have an immature phenotype, with low expression of major histocompatibility complex (MHC) class II and costimulatory molecules and a decreased capacity to present antigen in vitro (20,27). In view of the defective production of MCP-1 in the Tg mice, dendritic cells could potentially have failed to accumulate in the lungs in response to C. neoformans infection because of defective CCR2-mediated recruitment and differentiation of monocytes (46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diseases of the lung (lymphocytic interstitial pneumonitis), heart (myocytolysis and myocarditis), and kidney (tubulointerstitial nephritis, segmental glomerulosclerosis, and microcystic dilatation) develop in these Tg mice (19,24). Mucosal Candida infection in these Tg mice closely mimics the clinical and pathological features of candidal infection in human HIV infection (18,25) and has allowed us to perform controlled studies on the immunopathogenesis of mucosal candidiasis in HIV infection (26)(27)(28).…”
mentioning
confidence: 99%
“…We found that the five newly generated HIV Tg strains ϩ T-cell cocultures in vitro (63). Therefore, successful control of C. albicans in the oral mucosa of the normal host likely requires the participation and interaction of both of these cell populations.…”
Section: Discussionmentioning
confidence: 97%
“…The likelihood of such a defect was considered significant because CD4 ϩ T cells are quantitatively and functionally defective in these Tg mice, and these alterations of CD4 ϩ T cells determine at least in part the susceptibility of these animals to chronic carriage of C. albicans (37). We found that macrophages from these Tg mice display a polarization toward an alternatively activated phenotype and are successfully recruited to the mucosa in response to C. albicans.…”
mentioning
confidence: 84%
“…Using a model of mucosal Candida infection in transgenic (Tg) mice expressing HIV-1 Nef in CD4 ϩ T cells, dendritic cells, and macrophages which closely mimics the clinical and pathological features of candidal infection in human HIV infection (14), we have previously shown that altered CD4 ϩ T-cell phenotype and function determine the susceptibility to chronic carriage of C. albicans in these Tg mice (37). However, PMNs from the Tg mice were unimpaired in their capacity to produce an oxidative burst and to phagocytose and kill C. albicans in vitro, and depletion of PMNs in these Tg mice did not alter the oral or gastrointestinal burdens of C. albicans or cause systemic dissemination (42).…”
mentioning
confidence: 99%